Low-Dose 5-Aza and DZnep Alleviate Acute Graft-Versus-Host Disease With Less Side Effects Through Altering T-Cell Differentiation - Wang, Qing Ya; Liu, Hui Hui; Dong, Yu Jun; Liang, Ze Yin; Yin, Yue; Liu, Wei; Wang, Qing Yun; Wang, Qian; Sun, Yu Hua; Xu, Wei Lin; Han, Na; Li, Yuan; et al. (Frontiers in Immunology, 2022)
Objective: Previous studies showed hypomethylating agent (HMA) could alleviate acute graft versus host disease (aGvHD) but affect engraftment after allo-HSCT. Combination of two different HMAs with lower doses might overcome the problem. This study aims to evaluate the treatment effect of the combined two HMAs azacitidine (5-Aza) and histone H3K27 methyltransferase inhibitor 3-deazaneplanocin (DZNep) for the prophylaxis of aGvHD after allo-HSCT and explore the possible mechanisms. Methods: We first optimized the concentrations of individual and combinational 5-Aza and DZNep to ensure no obvious toxicities on activated T cells by evaluating the T cell proliferation, viability and differentiation. Mouse model of aGvHD was then established to assess the prophylactic efficacy of 5-Aza, DZNep and their combination on aGvHD. Immunomodulatory effect on T cells and hematopoietic reconstruction were assessed. Additionally, RNA sequencing (RNA-seq) was performed to identify the underlying molecular mechanisms. Results: Compared with single treatment, in vitro application of 5-Aza with DZNep could more powerfully reduce Th1/Tc1 production and increase Treg production. In an allo-HSCT mouse model, in vivo administration of 5-Aza with DZNep could enhance prophylactic effect for aGVHD compared with single agent. Mechanism study demonstrated that combination of 5-Aza and DZNep in vivo has an enhanced effect to inhibit Th1/Tc1 production, increase Th2/Tc2 proportion, and induce Treg differentiation as in vitro. RNA-seq analysis revealed that cytokine and chemokine pathways as one mechanism for alleviation of aGvHD with 5-Aza and DZNep combination. Conclusion: Combination of 5-Aza with DZNep could enhance prophylactic effect for aGvHD by influencing donor T cell differentiation through affecting cytokine and chemokine pathways. This study shed a light on the effectively prophylactic measure for aGvHD by using different epigenetic agent combination.